Efficacy and safety assessment of different dosage of benznidazol for the treatment of Chagas disease in chronic phase in adults (MULTIBENZ study): Study protocol for a multicenter randomized Phase II non-inferiority clinical trial - Molina Morant, D. (2020)
Background: Chagas disease (CD) continues to be a neglected infectious disease with one of the largest burdens globally. Despite the modest cure rates in adult chronic patients and its safety profile, benznidazole (BNZ) is still the drug of choice. Its current recommended dose is based on nonrandomized studies, and efficacy and safety of the optimal dose of BNZ have been scarcely analyzed in clinical trials.Methods/design: MULTIBENZ is a phase II, randomized, noninferiority, double-blind, multicenter international clinical trial. A total of 240 patients with Trypanosoma CD in the chronic phase will be recruited in four different countries (Argentina, Brazil, Colombia, and Spain). Patients will be randomized to receive BNZ 150 mg/day for 60 days, 400 mg/day for 15 days, or 300 mg/day for 60 days (comparator arm). The primary outcome is the efficacy of three different BNZ therapeutic schemes in terms of dose and duration. Efficacy will be assessed according to the proportion of patients with sustained parasitic load suppression in peripheral blood measured by polymerase chain reaction. The secondary outcomes are related to pharmacokinetics and drug tolerability. The follow-up will be 12 months from randomization to end of study participation. Recruitment was started in April 2018.Conclusion: This is a clinical trial conducted for the assessment of different dose schemes of BNZ compared with the standard treatment regimen for the treatment of CD in the chronic phase. MULTIBENZ may help to clarify which is the most adequate BNZ regimen in terms of efficacy and safety, predicated on sustained parasitic load suppression in peripheral blood.